2020
DOI: 10.3389/fnbeh.2020.556645
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Postrhinal and Perirhinal Cortices in Microscale and Macroscale Visuospatial Information Encoding

Abstract: Whereas the postrhinal cortex (POR) is a critical center for the integration of egocentric and allocentric spatial information, the perirhinal cortex (PRC) plays an important role in the encoding of objects that supports spatial learning. The POR and PRC send afferents to the hippocampus, a structure that builds complex associative memories from the spatial experience. Hippocampal encoding of item-place experience is accompanied by the nuclear expression of immediate early gene (IEGs). Subfields of the Cornus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 94 publications
(228 reference statements)
2
14
0
Order By: Relevance
“…Effects were distinct from the control condition where animals simply remained stationary and at rest in one corner of the experimental chamber. Behavioral data were also reported in Sethumadhavan et al (2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Effects were distinct from the control condition where animals simply remained stationary and at rest in one corner of the experimental chamber. Behavioral data were also reported in Sethumadhavan et al (2020).…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of somatic Arc expression triggered by the behavioral paradigms used revealed that Arc mRNA expression differs significantly between the experimental groups (multifactorial ANOVA: F (2,245) = 17.7158, p < 0.00001, Table 3). Post hoc analysis revealed that novel object exploration enhances item learning results in an increase in Arc mRNA expression in layer II of the caudal area 35 after macroscale item learning (Sethumadhavan et al, 2020). In the present study, a different imaging technique was used and a larger proportion of nuclei was analyzed in layer II (Figure 2, Table 1).…”
Section: Novel Object Learning Changes Nuclear Arc Mrna Expression In the Perirhinal Cortexmentioning
confidence: 86%
See 2 more Smart Citations
“…Spatial representations in the dorsal, or Where, cortical stream for spatial representation and action go through postrhinal cortex and MEC on their way to hippocampal cortex, whereas object representations in the ventral, or What, cortical stream for perception and object recognition go through perirhinal cortex and LEC on their way to hippocampal cortex ( Hargreaves et al, 2005 ; Norman and Eacott, 2005 ; Aminoff et al, 2007 ; Kerr et al, 2007 ; Eichenbaum and Lipton, 2008 ; van Strien et al, 2009 ; LaChance et al, 2019 ; Nilssen et al, 2019 ; Sethumadhavan et al, 2020 ), where they are merged.…”
Section: Introduction: Hippocampal Learning Theta Rhythm and Cholinergic Modulationmentioning
confidence: 99%